Research on the characteristics of Chinese film bullet chat and audience's use motivation from the perspective of streaming media - Wan, Su; Habil, Hadina (Edelweiss Applied Science and Technology, 2025)
Based on the cultural communication attributes of film bullet chat, this paper uses communication theories such as "use and satisfaction," "communication effect," and "spiral of silence," and adopts in-depth interviews and online participant observation methods to study the phenomenon of Chinese film bullet chat from the perspective of streaming media. The study found that the bullet chat in Chinese movies has the characteristics of fun, short expression, interactivity, and language carnival. The motives of bullet chat audiences are mainly to seek entertainment, express emotions and identity, and participate in interaction and social needs, among others. The results of this study help to enhance the existing research findings and to supplement the relevant theory.